The critical grain size for optimal strength–ductility synergy in CrCoNi medium entropy alloy. (September 2022) - Guo, F.J.; Wang, Y.F.; Wang, M.S.; Wei, W.; He, Q.; Wang, Q.Y.; Huang, C.X.; Jin, R.R.
Abstract: In metals with homogeneous microstructure, whether there is a critical grain size, and exactly at which, that enables the optimal strength-ductility synergy alongside the trade-off relation? Here, this issue is investigated in the recrystallized CrCoNi medium entropy alloys across a wide grain size range of 0.23-108 μm. Results reveal that there is indeed a critical grain size of ∼2 μm at which the product of yield strength (∼800 MPa) and uniform elongation (>30%) reaches the maximum, i.e., achieving the optimal strength-ductility synergy. Physics behind this critical grain size are explored by microstructure examination: ( i ) reduced grain size renders short dislocation slip path for high strength; ( ii ) low initial dislocation density and dense grain/twin boundaries enables effective accumulation of defects for consistent work hardening during plastic deformation. graphical abstract: Image, graphical abstract